POTENTIAL CONTENT OF ENERGY MATERIAL FOR EMPOWERING ENVIRONMENTAL AWARENESS IN SCIENCE LESSON IN ELEMENTARY SCHOOL TEACHER CANDIDATE - Siti Patonah; Sentot Budi Rahardjo; Cari Cari; Sajidan Sajidan (Universitas Sebelas Maret, 2018)
Environmental damage is increasingly worrisome, requiring basic handling. Among the important roles in the process of preparing human resources that have environmental concerns is through education. Especially in basic education. Therefore preparing prospective elementary school teachers who can undertake the task of preparing future resources that have environmental concerns becomes an urgent need. The process of preparing teachers to have environmental concerns can be taught through energy learning. The subject / unit about energy is an option because the discussion is very close to everyday life.